A case of pneumatosis cystoides intestinalis in connective tissue disease. Issue 4 (November 2016) - Fung, Arthur MY; Ng, Ka‐Chun; Tsui, Wilson MS; Wong, Kwok‐Wa
Abstract : Pneumatosis cystoides intestinalis (PCI) with spontaneous pneumoperitoneum is a rare but important condition in patients with connective tissue disease. In the present study, we report on a woman with mixed connective tissue disease who presented with PCI, and subsequently symptoms, of chronic intestinal pseudo‐obstruction. Prompt surgical resection of the bowel segment with pneumatosis should be considered to prevent a condition of gas leakage from turning into full‐blown chemical peritonitis.